STABILITY CALCULATION OF SOIL RETAINING WALL HANDLING LANDSLIDES SUNGAI PAYANG SECTION ROAD KABUPATEN KUTAI KARTANEGARA - HEVI ERIVANA, FEDI (KURVA S JURNAL MAHASISWA, 2014)
Landslide that occurred on the road or the road that experienced landslides, must be addressed so that it does not interfere with the performance of the road which is the lifeblood and driving force of development. Sungai Payang roads in District Loa Kulu, an alternative road that connects the subdistrict Loa Kulu District of the City and District Build Sebulu , but these roads are areas prone to landslides, this is due to topographical conditions of these roads which form hilly areas, mining and agricultural region . Lack of supporting vegetation buffer zones rainwater and make this area very prone to landslides in the event of rain, so that at some point the road had seen the potential for landslides and seeds, which requires extra care and handling of fast, responsive and accurate prior to the occurrence of landslides around the position of the road.Handling avalanche course requires an analysis and technical studies , detailed and comprehensive, so it can produce a design that is appropriate and effective in order to conform with the original purpose of the handling of avalanches can be achieved. From the calculation results can be concluded that the dimensions of the wall pehanan high ground with 3 meter, a width of 1 meter, the upper wall thickness of 0,30 meters, the bottom wall thickness of 1,0 meters, 0,30 meters thick conterfort, the distance between conterfort 1,50 meters long, 10 meters per segment review . Secure the stability of a retaining wall to bolster however affect the shear, so that the necessary foundation piles with additional bracing to the pile group to rigidify the structure of the walls and the pile. Reinforcement retaining wall using a diameter of 13 mm, 16 mm, 19 mm and 22 mm .